Patient-centered Bedside Education and Traditional Jewish Law and Ethics - Yigal Shafran; Joel B. Wolowelsky (Rambam Maimonides Medical Journal, 2012)
Background Bedside rounds have long been a time-honored component of medical education. Recently, there have been various recommendations that residency-training programs further incorporate bedside teaching into clinical curricula. Objectives To compare these current attitudes regarding bedside education with the position of traditional Jewish law and ethics. Methods Relevant medical journal articles and traditional Jewish sources were reviewed. Results Halacha (the corpus of traditional Jewish law and ethics) gives greater focus to a patient-centered rather than student-centered bedside education experience. Conclusion Residency training programs should give greater consideration to the importance of a patient-centered bedside education experience.